2016
DOI: 10.1021/acs.biochem.5b01204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of the Homotrimeric Sliding Clamp of T4 Phage: Two Domains of a Subunit Display Asymmetric Characteristics

Abstract: Sliding clamp proteins are circular dimers or trimers that encircle DNA and serve as processivity factors during DNA replication. Their presence in all the three domains of life and in bacteriophages clearly indicates their high level of significance. T4 gp45, besides functioning as the DNA polymerase processivity factor, also moonlights as the late promoter transcription determinant. Here we report a detailed biophysical analysis of gp45. The chemical denaturation of gp45 probed by circular dichroism spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…gp45 unfolds after a three-state transition with unfolding of NTD preceding CTD (52). We have previously shown that gp45 CTD undergoes MG-like intermediate formation during unfolding and refolding; here, CTD alone adopts MG conformation, whereas the NTD remains unfolded (52). In this article, we show that there occurs a huge conformational rearrangement in the gp45 CTD when it forms MG. Our data suggest that the domain swells and forms DMG wherein the surface residues flip inside the domain's hydrophobic core, causing burying of residues in a solventexcluded environment.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…gp45 unfolds after a three-state transition with unfolding of NTD preceding CTD (52). We have previously shown that gp45 CTD undergoes MG-like intermediate formation during unfolding and refolding; here, CTD alone adopts MG conformation, whereas the NTD remains unfolded (52). In this article, we show that there occurs a huge conformational rearrangement in the gp45 CTD when it forms MG. Our data suggest that the domain swells and forms DMG wherein the surface residues flip inside the domain's hydrophobic core, causing burying of residues in a solventexcluded environment.…”
Section: Introductionmentioning
confidence: 58%
“…The cloning of various genes, protein expression and purification, and sitedirected mutagenesis were carried out as described previously (52), and are detailed in Supporting Material. Proteins were dialyzed against gp45 buffer (50 mM sodium phosphate pH 7.4, 50 mM NaCl, 1 mM EDTA, and 5% glycerol).…”
Section: Site-directed Mutagenesis Cloning and Protein Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…S1. Molar ellipticity values at 222 nm were recorded and used to calculate fraction unfolded as described elsewhere . The unfolding transition of LD WT and its variants was also monitored using Differential scanning calorimetry on a Microcal VP‐DSC (GE Healthcare, Chicago, IL, USA) as detailed in Doc.…”
Section: Methodsmentioning
confidence: 99%